Monitoring Coastal Line Changes Using the Digital Shoreline Analysis System (DSAS) Method in the Coastal Area of Mekkatta Village, Mejene Regency - Asri, Haryanto; Novitasari, Femiliani (Hasanuddin University, 2023)
Analysis of coastline changes in Mekkata Village from 2013 to 2023 was conducted using the baseline of the nearest coastline to the mainland. This baseline was used as a reference point for transects measuring changes. The shoreline encompasses the coastline during the research period. Net Shoreline Movement (NSM) was employed to differentiate between erosion and accretion in the study area, showing an average shoreline change value of -9.72 meters towards the mainland, indicating predominant erosion. According to DSAS, it is observed that the coastline of Mekkata Village experienced erosion along 41 transects, while 31 transects exhibited accretion, highlighting significant changes. The most notable erosion area was identified along transects 60, 61, and 62, indicating consistent land reduction. Meanwhile, the most accretion-prone transects were 11, 12, and 13, signifying substantial land addition. The predominant erosion process is suspected to be influenced by the gentle slope of the coastal area and the composition of sand material. Human activities such as deforestation and river mouths also contribute to erosion. The absence of coastal protection structures allows direct waves and currents to impact the shore, potentially causing erosion. Meanwhile, accretion areas around river mouths indicate the formation of emergent land or deltas.